Timing of Intubation in Coronavirus Disease 2019: A Study of Ventilator Mechanics, Imaging, Findings, and Outcomes - Avni A. Bavishi, MD, MS (Wolters Kluwer, 2021)
Objectives:. Determine the variation in outcomes and respiratory mechanics between the subjects who are intubated earlier versus later in their coronavirus disease 2019 course. Design:. Retrospective cohort study. Setting:. Northwestern Memorial Hospital ICUs. Patients:. All patients intubated for coronavirus disease 2019 between March 2020 and June 2020. Interventions:. Patients were stratified by time to intubation: 30 subjects were intubated 4–24 hours after presentation and 24 subjects were intubated 5–10 days after presentation. Baseline characteristics, hospitalization, ventilator mechanics, and outcomes were extracted and analyzed. Ten clinically available CT scans were manually reviewed to identify evidence of pulmonary vascular thrombosis and intussusceptive angiogenesis. Measurements and Main Results:. Median time from symptom onset to intubation was significantly different between the early and late intubation cohorts, with the latter being intubated later in the course of their illness (7.9 vs 11.8 d; p = 0.04). The early intubation cohort had a lower mortality rate than the late intubation cohort (6% vs 30%, p < 0.001) without significantly different respiratory mechanics at the time of intubation. The late intubation cohort was noted to have higher dead space ratio (0.40 vs 0.52; p = 0.03). On review of CT scans, the late intubation cohort also had more dilated peripheral segments on imaging (two segments vs five segments). Conclusions:. The question as to whether delaying intubation is beneficial or harmful for patients with coronavirus disease 2019-induced hypoxemic respiratory failure has yet to be answered. As our approaches to coronavirus disease 2019 continue to evolve, the decision of timing of intubation remains paramount. Although noninvasive ventilation may allow for delaying intubation, it is possible that there are downstream effects of delayed intubation that should be considered, including the potential for pulmonary vascular thrombosis and intussusceptive angiogenesis with delayed intubation.